Effects of Elastic Hinges on Input Torque Requirements for a Motorized Indirect-Driven Flapping-Wing Compliant Transmission Mechanism - Chao Zhang; Claudio Rossi (IEEE Access, 2019)
This paper presents compliant transmission mechanisms for a flapping-wing micro air vehicle. The purpose of this mechanism is to reduce power consumption, a critical issue in this kind of vehicles, as well as to minimize the peak input torque required by the driving motor, which helps to maintain flight stability and reduces mechanical shocks of the structure. We first describe the development of pseudo-rigid-body model of the mechanism and the analysis of the corresponding kinematics. Second, we compute the required input torque for driving stable flapping motions, from the perspectives of work and energy. For this computation, two methods are applied, one based on the principle of virtual work and another one based on rigid-body dynamics. Our mathematical analysis demonstrates that both methods are consistent with each other in terms of the resulting input torque from the motor. Finally, according to the results from the input torque analysis, the main parameters characterizing the compliant joints, the torsional stiffness of virtual spring and initial neutral angular position, are optimized. The experimental results carried out with two different mechanical setups, one with rigid components, and another one with flexible components, demonstrate the relationship between the input voltage (that is directly related to flapping frequency) and power saving of the compliant mechanism. The average power consumption is reduced of up to 4%, and peak power consumption is reduced up to 25% using the compliant transmission mechanisms compared to the rigid mechanism. The experiments also show a clear relationship between flapping frequency and power savings.